Ayatollah Khomeini - Gordon, Matthew (New York Chelsea House Publishers, 1988)
An illustrated biography of the Islamic religious leader who became the chief political figure in Iran after the overthrow of the shah in 1979.
Cover title: Khomeini.
Includes index.
Bibliography: p. 112.
Keywords: Khomeini, Ruhollah -- Juvenile literature; Khomeini, Ruhollah; Islam -- Biography; Iran -- History -- 1979-1997 -- Juvenile literature; Iran -- History -- Mohammad Reza Pahlavi, 1941-1979 -- Juvenile literature; Iran -- History -- 1979-1997.